Single Parents Competing in a Dual-Earner Society: Social Policy to Level the Playing Field. (July 2022) - Nieuwenhuis, Rense
I examine the relative poverty risk among single-parent households in countries that have a large share of households with dual earners. Data from the Luxembourg Income Study (LIS) Database are used to analyze eighteen OECD countries in the period 1984 to 2010. I find that single parents face higher relative income poverty risks in countries with a large share of dual-earner households and that this higher risk of poverty is related to higher standards of living in those countries: higher standards of living have raised poverty thresholds, and single-parent incomes are less likely to reach those higher poverty thresholds. I also find that this overall pattern varied across institutional contexts: a rise of dual-earner households puts single parents at a disadvantage only in countries that have relatively low public expenditures on childcare and relatively low income transfer policies.